The Detection of H pylori In Gastric Mucosal Biopsy Specimens by PCR Using Primers Derived From Ure C Gene in Patients with Dyspepsia - Soewignjo Soemohardjo; I Gede Palgunadi; S Gunawan; Zainul Muttaqin; Haris Widita; Wenny Astuti A (The Indonesian Society for Digestive Endoscopy, 2007)
Background: The detection of Helicobacter pylori (H. pylori) in gastric biopsy specimens can be done using CLO (Campylobacter Like Organism) test and histopatological examination, but the sensitivity of both Method is influenced by the density of the bacteria in the sample. Beside that, the coccoid form is detected with difficulty by histology and need immunohistochemical stain to confirm. PCR can be used for the detection of both spiral and coccoid form of the bacteria. Objective: To detect the genome of H. pylori by Polymerase Chain Reaction (PCR) using primers derived from ureC gene of the bacteria in gastric biopsy specimen from patients with dyspepsia. Methods: Gastric biopsy specimen from 179 patients with dyspepsia in the endoscopic unit Mataram hospital. The biopsy was taken from antrum and corpus and put into sterile saline for the culture of H. pylori and put into 70% ethanol solution for the PCR. The specimen for bacterial culture was carried soon to microbiology laboratory and plated into the appropriate media and grown in microaerophilic condition in CO2 incubator. The PCR was done using primers derived from ureC. Result: The H. pylori genome was detected in 79 of 179 biopsy sample (44.13%). The bacterial culture was positive for H. pylori in 22 (12%). The PCR result was positive in 10/35 of patient with normal endoscopy (28.57%). From 22 patients with duodenal ulcer without gastric ulcer the PCR was positive in 15 (68.18%). In patient with gastric ulcer without duodenal ulcer the PCR was positive in 9 patients (42.08%). From 7 patient with combined gastric and duodenal ulcer the PCR was positive in 5 (71.43%), in 3 patient with gastric cancer the PCR was positive in 1 (33.33%). Conclusion: The study showed that 44.13% of patient with dyspepsia in Mataram hospital was positive for H. pylori by PCR. Keywords: detection of Helicobacter pylori, gastric mucosal biopsy specimen, polymerase chain reaction, ureC gene